2007
DOI: 10.1590/s0482-50042007000500017
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento de estenose de tronco de coronária esquerda na arterite de Takayasu

Abstract: 50%) no tronco de coronária esquerda, sendo indicada, a princípio, angioplastia coronariana com implante de stent. Após 3 meses, realizou-se cirurgia de revascularização miocárdica em razão de reestenose. A isquemia miocárdica é uma causa importante de óbito e deve ser prontamente tratada. A abordagem percutânea pode ser a primeira escolha ou servir como ponte para a cirurgia.]]>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…The inflammatory process of the aorta has been identified as being responsible for these lesions, in which the occlusion of the ostium of the coronary arteries occurs more often, though there are many cases in the literature that describe coronary arteritis with no occlusion of the ostium. 13,14 Coronary artery involvement in this patient is similar to that described by Endo et al, in which 24 patients presented coronary artery stenosis, of whom 83.3% were women. 12 According to angiographic findings, the TA was classified in six types of alterations based on the affected region, which is useful for surgical planning.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The inflammatory process of the aorta has been identified as being responsible for these lesions, in which the occlusion of the ostium of the coronary arteries occurs more often, though there are many cases in the literature that describe coronary arteritis with no occlusion of the ostium. 13,14 Coronary artery involvement in this patient is similar to that described by Endo et al, in which 24 patients presented coronary artery stenosis, of whom 83.3% were women. 12 According to angiographic findings, the TA was classified in six types of alterations based on the affected region, which is useful for surgical planning.…”
Section: Discussionsupporting
confidence: 87%
“…16 Due to a serious chance of intra-stent restenosis, cardiac magnetic resonance (CMR) is the procedure of choice to treat coronary artery lesions. 14 In a retrospective case series involving 106 Japanese patients, Miyata et al 17 observed a 15-year increase in the survival rate, rising from 43% (among those treated with medical therapy) to 67.5% after the addition of surgical intervention. Yang et al, 18 in an analysis of 31 patients with TA who underwent revascularization by CMR (12) and PCI (19), in an average follow-up of 101 months, observed higher restenosis rates in the percutaneous group.…”
Section: Discussionmentioning
confidence: 99%
“…O processo inflamatório da aorta tem sido identificado como responsável por essas lesões em que a oclusão dos óstios das coronárias ocorre com maior frequência, embora existam vários casos descritos de arterite coronária sem oclusão do óstio. 13,14 O envolvimento das coronárias nesta paciente é similar ao descrito por Endo et al, em que 24 pacientes tiveram estenose coronária, sendo que 83,3% destes eram mulheres. 12 De acordo com os achados angiográficos, a AT foi classificada em 6 tipos de alterações com base na região de acometimento, o que é útil para o planejamento cirúrgico.…”
Section: Discussionunclassified
“…16 Devido à grande chance de reestenoses intra-stents, a CRM é o procedimento de escolha para o tratamento das lesões coronarianas. 14 Em uma série de casos retrospectivos envolvendo 106 pacientes japoneses, Miyata et al, 17 observaram um aumento na taxa de sobrevida em 15 anos de 43% (naqueles tratados com terapia médica) para 67,5% após a adição de cirurgia intervenção.…”
Section: Discussionunclassified
“…In the literature, the presence of some type of coronary disease is described in 6% to 30% of patients with TA [1][2][3][4] . Its pathogenesis is not yet completely understood and is currently considered the result of chronic autoimmune inflammation of large arteries, in addition to being associated with other factors, such as infectious agents and genetic predisposition.…”
Section: Discussionmentioning
confidence: 99%